Proposing an Integrated Islamic Microfinance Model in Alleviating Poverty and Improving the Performance of Microenterprises in Indonesia - Hawariyuni, Weni; Salina, Kassim (Accounting Department, Faculty of Economics and Business, Universitas Syiah Kuala, 2019)
Objective – This study proposes an integrated Islamic microfinance model in alleviating poverty and improving the performance of microenterprises based on a case study of Indonesia, by focusing specifically on BRI Microbanking.